2020
DOI: 10.38025/2078-1962-2020-97-3-31-39
|View full text |Cite
|
Sign up to set email alerts
|

Abilities of physical rehabilitation in pneumonia

Abstract: The use of physical rehabilitation methods, in particular respiratory rehabilitation for pneumonia, allows to increase the tolerance to physical activity, improve oxygen consumption and endurance of patients compared to the initial level, reduce the frequency and duration of their hospitalization, as well as significantly improve the effectiveness of drug therapy. In the first stage of assisting patients with pneumonia of various genesis, therapeutic exercises are recommended that improve drainage function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…[21][22] The data obtained indicate the high efficiency and significance of controlling online exercise therapy sessions for patients. 23,24 This project for ex-COVID-19 patients has the following qualitative results: improvement of quality of patients' life; timely dynamic monitoring and timely referral to relevant experts; speeding of restoration process after treatment; psychological support; prevention of secondary complications; reduction of severe adverse effects of treatment; lightening of burden on family members and guardians. The Russian Healthcare System might be interested in the following results of this project: reduction of disability periods; reduction of rehospitalization rates; decreased need in additional support; lower disability.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22] The data obtained indicate the high efficiency and significance of controlling online exercise therapy sessions for patients. 23,24 This project for ex-COVID-19 patients has the following qualitative results: improvement of quality of patients' life; timely dynamic monitoring and timely referral to relevant experts; speeding of restoration process after treatment; psychological support; prevention of secondary complications; reduction of severe adverse effects of treatment; lightening of burden on family members and guardians. The Russian Healthcare System might be interested in the following results of this project: reduction of disability periods; reduction of rehospitalization rates; decreased need in additional support; lower disability.…”
Section: Resultsmentioning
confidence: 99%
“…Tang Jun guided the dust lung patient for functional exercise (abdominal breathing) month, and the results show that the patient's conscious chest tightness, shortness of breath, difficulty breathing, and so forth; the lung ventilation; and ventilation function have been improved. Tsyganova et al showed that breathing exercise can effectively improve the quality of life of patients with dustpiculmonary [ 3 ]. Fang, for the first-month respiratory function exercise for patients with case-free pulmonary fibrosis, compared the clinical symptoms, quality of life, and blood gas analysis before and after exercise, and the results show that the above indicators have improved, so they think that breathing function is special.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Задачи физической реабилитации: улучшить вентиляцию здоровой легочной ткани для активного включения ее в функцию внешнего дыхания; улучшить дренажную функцию бронхов; улучшить крово-и лимфообращение в пораженной доле легкого; профилактика возникновения ателектазов, спаечного процесса; ускорить процессы рассасывания при воспалительных процессах в легочной ткани [23].…”
Section: физическая реабилитацияunclassified
“…При острой пневмонии средней и тяжелой степени тяжести показано как применение красного лазерного излучения с длиной волны 0,63 мкм на очаг поражения, так и внутрисосудистое облучение [23,25].…”
Section: обзоры и лекцииunclassified